Explaining variations in absence rates: temporary and agency workers in the food manufacturing sector. (26th October 2012) - Hopkins, Benjamin
<x xml:space="preserve">Abstract</x> This article responds to a recent call in a provocation article in the Human Resource Management Journal by Thompson to use workplace studies to investigate employees' experiences of HR practices. Examining the particular case of absence management, the article investigates the experiences of short‐term workers in the food manufacturing industry in the UK. Variations in absence rates between directly employed temporary workers and agency workers are shown to be the result of differing levels of managerial control over absence, which affects workers' ability to use absence as a form of industrial conflict to escape a low‐skilled and monotonous work process.